Peningkatan Keterampilan Sosial Siswa Autis Melalui Teknik Shaping - Anggriana, Tyas Martika; Kadafi, Asroful; Trisnani, Rischa Pramudia (Jurnal Fokus Konseling, 2018)
Social skills in Children with Special Needs are very important. Autistic students who have high social skills will have high self-esteem and are easy to socialize with their environment. However, in reality, many autistic children who have low social skills are found. From this case, it is necessary to have a special treatment that can be started from formal education to improve the social skills of disabled students. One way that can be done by school counselors is using shaping techniques to grow social skills. This study uses the pre-experimental design method. The design of this study uses One Group Pretest-Posttest Design. From the results of the data analysis technique using Wilcoxon signed ranks test, it was found that z-score was -2,366 with a significance level of 0.018, which means there were differences in the results of the pretest and post-test results, where the post-test results were lower than the pre-test results. Thus it can be concluded that effective shaping techniques are used to improve social skills.Keywords:Â  shaping technique, social skills, autistic studentsÂ